Smoky, the cowhorse - James, Will 1892-1942 (New York Aladdin Paperbacks, 1926)
The experiences of a mouse-colored horse from his birth in the wild, through his capture by humans and his work in the rodeo and on the range, to his eventual old age.
"Winner of the Newbery Medal"
Ages 8-12.
Keywords: Horses -- Juvenile fiction; Horses -- Fiction; West (U.S.) -- Fiction